RELASI POLITIK ELITE LOKAL PESISIR DAN PETANI RUMPUT LAUT PADA PEMILU LEGISLATIF 2014 KOTA PALOPO - Armunanto, Ali (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2017)
This research aims to find out how the local elites of coastal area establishing political relation with the mass, especially with seaweed farmers and to determine the factors that influence. This research was conducted in Palopo city, South Sulawesi since November until December 2015 and used descriptive qualitative method. The primary data was obtained by interviewing some informants in Wara Utara district in Palopo as the first election’s district. To support the primary data, the researcher used secondary data that obtained from literature resources, documents, and articles related to this research.The result of this research shows that the political relation existed in the form of economical dependence, which was the exchange, including the products marketing and occupation field that was dominated by the local elites. The local elites gained benefits in terms of support in the legislative election 2014, so that they got position in DPRD (District Legislative Council) of Palopo city. The political relation was affected by calculation benefit of elites, dependence service of markets, and guaranted income by local elites in coastal area.